2020
DOI: 10.5194/egusphere-egu2020-20313
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The vertical structure of atmospheric rivers and their impact in the Atlantic sector of Antarctica from the Year of Polar Prediction observations

Abstract: <p>The Year of Polar Prediction in the Southern Hemisphere (YOPP-SH) had a special observing period (SOP) from November 16, 2018 to February 15, 2019, during which observational activity during austral summer in the Antarctic was greatly enhanced. More than 2000 additional radiosondes were launched during this 3-month period, roughly doubling the amount from routine programs. Further, several YOPP-endorsed projects contributed to enhanced data collection on various atmospheric and oceanic propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The low-pressure system affecting the Antarctic Peninsula during 6 December was associated with an atmospheric river event, with a significant temperature inversion in the lower troposphere apparent in the radiosounding at Escudero station. As Gorodetskaya et al (2020b) and Bromwich et al (2020) described, this temperature inversion layer also showed a significant moisture inversion, and a peak in the moisture flux observed at the Escudero station. This temperature inversion was not captured by the ERA5 temperature profile, while Polar-WRF data simulated it well, however, with a slight shift towards the lower heights.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…The low-pressure system affecting the Antarctic Peninsula during 6 December was associated with an atmospheric river event, with a significant temperature inversion in the lower troposphere apparent in the radiosounding at Escudero station. As Gorodetskaya et al (2020b) and Bromwich et al (2020) described, this temperature inversion layer also showed a significant moisture inversion, and a peak in the moisture flux observed at the Escudero station. This temperature inversion was not captured by the ERA5 temperature profile, while Polar-WRF data simulated it well, however, with a slight shift towards the lower heights.…”
Section: Discussionsupporting
confidence: 52%
“…Different temperature and precipitation characteristics were observed and simulated for the event on 6 December. Gorodetskaya et al (2020b) and Bromwich et al (2020) showed that this event was associated with an atmospheric river, affecting both southern South America and the Antarctic Peninsula. Radiosonde measurements at Escudero on 6 December 2018, 13 UTC, demonstrated a temperature inversion at around 800 hPa exceeding 0 °C at the inversion height and in the layer between it and the surface (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations